ACADEMIC PROCRASTINATION AMONG UNDERGRADUATE STUDENTS OF A MEDICAL INSTITUTION - Thapa, Kriti; Prasad Rimal, Surya (Journal of Chitwan Medical College, 2024)
Background: Academic procrastination is a universal phenomenon. It affects various aspects of student’s personal and academic life and also has been associated with numerous undesirable and irreversible consequences. The objective of the study was to assess the level of academic procrastination among the undergraduate students. Methods: A descriptive cross-sectional study was conducted among 454 undergraduate students of a medical institute using convenience sampling technique. Students were requested to complete a self-administered questionnaire which comprised their socio-demographic characteristics and Academic Procrastination scale. Descriptive studies i.e. mean, percentage, frequency, standard deviation and inferential statistics i.e. Chi-square was used to analyse the data. Results: High level of academic procrastination was seen among 40.1% of the undergraduate students. Academic procrastination was also found to be significantly associated with age, sex and academic year of the undergraduate students. Conclusions: The finding of this study reveal that a considerable number of undergraduate students have high level of academic procrastination.